A review on Parkinson’s disease symptoms before and after deep brain stimulation treatment - Maharjan, Reeju (Eastern Journal of Medical Sciences, 2022)
Introduction: Parkinson’s disease (PD), followed by Alzheimer’s disease, is the most common progressive neurodegenerative disease. Tremors, rigidity, akinesia, and disorders are common PD symptoms. Over the last few decades, deep brain stimulation (DBS) of the subthalamic nucleus has become a standard treatment for advanced PD. The aim of this systematic review paper is to see the difference between the symptoms of PD before and after DBS. Methods: We conducted a literature search using PubMed and Google Scholar. We chose research from the past 10 years. We retrieved 64 papers, and seven duplicated papers were removed. We reviewed the abstract for the remaining 57 papers which led to the selection of 29 papers. After applying inclusion and exclusion criteria for the remaining 29 papers, 23 papers in the English language were chosen for our review. Results: Five Randomized Clinical Trials (RCTs) studied the outcomes of DBS and eight RCTs about effects on posture and motor function. Four RCTs investigated the effects on gait and balance, two on tremors, and the remaining two on posture. The effects of DBS on speech and language were compared in two RCTs. Three studies looked at cognitive performance. One RCT studied sleeping versus awake DBS on PD. These studies showed that with DBS treatment, there was significant improvement in posture, motor function, gait, balance, speech, and language. However, more studies are required for the further analysis on dysphagia and urinary dysfunction. Conclusion: Our study contributed to a better understanding of the advantages of DBS for a range of symptoms, but it concluded that additional RCT on dysphagia and urinary dysfunction was required to reach a reliable conclusion. More research is required to determine the effects of DBS on different motor and non-motor PD symptoms to standardize treatment.